Abscisic Acid Mediates Drought-Enhanced Rhizosheath Formation in Tomato - Karanja, Joseph K.; Aslam, Mehtab Muhammad; Qian, Zhang; Yankey, Richard; Dodd, Ian C.; Weifeng, Xu (Frontiers in Plant Science, 2021)
The rhizosheath, commonly defined as soil adhering to the root surface, may confer drought tolerance in various crop species by enhancing access to water and nutrients in drying soil. Since the role of phytohormones in establishing this trait remains largely unexplored, we investigated the role of ABA in rhizosheath formation of wild-type (WT) and ABA-deficient (notabilis, not) tomatoes. Both genotypes had similar rhizosheath weight, root length and root ABA concentration in well-watered soil. Soil drying decreased root length similarly in both genotypes, but substantially increased root ABA concentration and rhizosheath weight of WT plants, indicating an important role for ABA in rhizosheath formation. WT plants had longer root hairs at a higher density, with soil drying decreasing root hair density and length similarly in both genotypes. In drying soil, root hair length was positively correlated with rhizosheath weight in both genotypes, while root hair density was positively correlated with rhizosheath weight in well-watered not plants. Root transcriptome analysis revealed that drought stress increased expression of ABA-responsive transcription factors such as AP2-like ER TF, alongside other drought-regulatory genes associated with ABA (ABA 8’-hydroxylase and protein phosphatase 2C). Thus root ABA status modulated the expression of specific gene expression pathways. Taken together, drought-induced rhizosheath enhancement was ABA-dependent, but independent of root hair traits.